Effect of deoiled corn dried distillers grains with solubles (solvent extracted) on growth performance, carcass characteristics, and carcass fat quality of growing and finishing pigs - J Y Jacela; K J Prusa; R C Thaler; D E Little; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 1,215 pigs (initially 65.2 lb) were used in a 99-d study to determine the effects of deoiled corn dried distillers grains with solubles, solvent extracted (dDGS) on growing and finishing pig growth performance, carcass characteristics, and carcass fat quality. Pigs were blocked on the basis of pen weight and randomly allotted to 1 of 5 dietary treatments containing either 0, 5, 10, 20, or 30% dDGS. Pigs were fed in 4 phases; all dietary treatments were formulated to similar dietary ME and standardized ileal digestible (SID) lysine concentrations within each phase. Choice white grease (CWG) was included at increasing amounts as dDGS increased in the diet to maintain uniform dietary ME. Overall (d 0 to 99), ADG and ADFI decreased (linear, P<0.01) with increasing dDGS in the diet. This reduction was especially pronounced when pigs were fed more than 20% dDGS. However, there was no difference in F/G (P>0.12) for pigs fed increasing dDGS. For carcass characteristics, carcass weight and percent yield were reduced (linear, P<0.01) and loin depth tended to decrease (P<0.09) with increasing dDGS. However, there were no differences in backfat (P<0.26), percent lean (P<0.16) or fat-free lean index (P<0.20). Jowl, backfat, and belly fat iodine values increased (linear, P<0.01) with increasing dDGS. These increases were expected because of the increasing CWG in diets with increasing dDGS. In summary, feeding increasing levels of dDGS lowered ADG and ADFI but did not affect F/G as a result of the added fat in the diet. These data confirm the accuracy of the previously determined ME (1,137 kcal/lb) and SID amino acid values for dDGS; however, reasons for the reduced ADFI need further investigation.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Deoiled corn; Dried distillers grains with solubles; Feed ingredient; Growth; Pork quality